LEARNING MOTIVATION IN THE STRUCTURE OF ACADEMIC ACHIEVEMENT OF MARITIME STUDENTS - Чумаєва, Юлія; Бельченко, Карина; Кара, Мілена (SWorldJournal, 2026)
The paper examines learning motivation of students of maritime specialties as an important psychological factor of academic achievement in the process of professional training. The specific features of training future maritime professionals-characterized